Stanje slovenske žagarske industrije v obdobju tranzicije - Merzelj, Franc (Les (Ljubljana), 1999)
Changed conditions of administration in the time of transition decisively influenced on state in saw-mill industry, so the number and largeness of saw-mills had been greatly changed. The main rule for those changes were leading by conditions of selling products and buying of raw materials. Changes are influenced also by common conditions of administration, which enabled fast and easy establishment of new enterprises. Saw-mill industry, which have tipical character of rural production, crumbled on numerous small saw-mills and season saw-mills of private forest owners. If we counted in the past saw-mill production as part of wood industry, we can now count it or we shall soon count it as forest wood production
Keywords: žagarstvo; žagarski obrat; Slovenia; Slovenija